Bystanders witnessing social exclusion exhibit reduced physiological responses of empathy: an EEG study - Torige, Satsuki; Yasumuro, Shinobu; Iwaki, Sunao (Frontiers in Psychology, 2025)
Bystanders play a crucial role in bullying interventions, with empathy serving as a key facilitator of bystanders’ helping behaviors toward victims. However, the physiological evidence linking bystanders’ empathic responses to prosocial behaviors is limited. In addition, differences in empathic responses between active and passive bystanders have not been investigated, although bystanders have been suggested to disengage from bullying depending on the situation. This study aimed to reveal how the involvement of bystanders modulates empathic responses while witnessing social exclusion using electroencephalography (EEG), specifically focusing on the changes in the amplitudes of frontal theta and alpha band spontaneous activities as indicators. Participants engaged in an Inclusion and Exclusion condition in two sessions of the Cyberball task: witness only and witness in participation. The results showed a significant main effect of the condition on theta band power (TBP), with a decrease in TBP while witnessing exclusion. Generally, the frontal theta power is amplified as an empathic response. However, the current results indicate that frontal theta power decreased by observing social exclusion, suggesting that, regardless of bystander situations, bystanders witnessing bullying may protect themselves by decreasing empathy or moral conflict.